2017
DOI: 10.1021/acs.jmedchem.6b01418
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Potent and Highly Selective Orexin 1 Receptor Antagonists with a Morphinan Skeleton and Their Pharmacologies

Abstract: Nalfurafine, a κ-selective opioid receptor agonist, unexpectedly showed a selective antagonist activity toward the orexin 1 receptor (OXR) (K = 250 nM). Modification of the 17-amino side chain of the opioid ligand to an arylsulfonyl group and the 6-furan acrylamide chain to 2-pyridyl acrylamide led to compound 71 with improvement of the antagonist activity (OXR, K = 1.36 nM; OXR, not active) without any detectable affinity for the opioid receptor. The dihydrosulfate salt of 71, freely soluble in water, attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 83 publications
(79 reference statements)
0
23
0
Order By: Relevance
“…SRI-9342 (irreversible antagonist, Scheme 1) was synthesized in 44% yield via the reaction of naltrexone hydrochloride and trans-4-hydrazino-2-stilbazole dihydrochloride following the same procedures previously reported [18,19]. SRI-45128 (inverse agonist, Scheme 2) was synthesized in nine steps by using reported procedures [20] with a few modifications. In our alternative route, the protecting group on the phenolic hydroxyl group of naltrexone (1) was changed from methyl to benzyl to achieve overall improved yields.…”
Section: Synthesis Of Novel Dor Irreversible Antagonist and Inverse Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…SRI-9342 (irreversible antagonist, Scheme 1) was synthesized in 44% yield via the reaction of naltrexone hydrochloride and trans-4-hydrazino-2-stilbazole dihydrochloride following the same procedures previously reported [18,19]. SRI-45128 (inverse agonist, Scheme 2) was synthesized in nine steps by using reported procedures [20] with a few modifications. In our alternative route, the protecting group on the phenolic hydroxyl group of naltrexone (1) was changed from methyl to benzyl to achieve overall improved yields.…”
Section: Synthesis Of Novel Dor Irreversible Antagonist and Inverse Agonistsmentioning
confidence: 99%
“…On the basis of NMR, HPLC-DAD, and HRMS (mass error less than 5 ppm), all final compounds were ≥95% pure. This compound was synthesized as previously described [18,19] This compound was synthesized by a modified procedure of the reported method [20] as described below. To a suspension of naltrexone (1) (5 g, 14.6 mmol) in acetone (200 mL), benzyl bromide (2.6 mL, 21.9 mmol) and potassium carbonate (4.0 mg, 29.3 mmol) were added.…”
Section: Chemical Synthesis and Characterizationmentioning
confidence: 99%
“…It appears that OX1R may be particularly implicated in these behaviours. A number of 1‐SORAs have been discovered (Bonaventure, Yun, et al., ; Nagase et al., ; Raheem et al., ; Stump et al., ), and currently the 1‐SORA, EORA101, is reportedly being evaluated as a potential therapeutic agent for smoking cessation (Eolas Theapeutics, ), although no clinical trials are listed on clinicaltrials.gov. A study is investigating the effects of suvorexant on cocaine craving (Table ).…”
Section: Other Neuropsychiatric Indications Being Explored With Orasmentioning
confidence: 99%
“…8 Recently, we found that the κ opioid receptor agonist nalfurafine showed a moderate activity and high selectivity toward OX1R, and we also synthesized the more potent OX1R antagonist YNT-707 (1) (Figure 1). 9 In these studies, we focused on how the specific character of the 4,5-epoxy-morphinan skeleton contributes to the remarkable OX1R selectivity and studied the essential structural sites required for binding to OX1R in the morphinan compounds based on 1. Our analyses showed that the specific conformation of the N17 functional group and C6 amide side chain are essential for the OX1R activity (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…8a-hexahydroisoquinoline-2(1H)-carboxylate(9). To a solution of 8 (13.0 g, 42.0 mmol) in MeOH (130 mL) was added 1 M aqueous NaOH solution (50 mL) and the mixture was stirred for 6.5 h at 50 °C under an argon atmosphere.…”
mentioning
confidence: 99%